Measuring the prevalence of adult sexual violence in Ireland: A review of Irish and international literature - Kelly, Elish; Agostinelli, Delia; Nolan, Anne; Smyth, Emer (ESRI, 2025)
Sexual violence (SV), and gender-based violence (GBV) more generally, is a pervasive global problem. While women and girls are most affected, sexual violence affects all sections of society, with profound consequences for the physical, psychological and economic wellbeing of both victims and their families. In Ireland, the recently established statutory agency Cuan co-ordinates and drives the implementation of Zero Tolerance, the third national strategy for domestic, sexual and gender-based violence (DSGBV). In this context, Cuan and the Economic and Social Research Institute (ESRI) have established a joint research programme to provide evidence to inform DSGBV policy development. The purpose of this report, the first in a series of reports from the research programme, is to provide an overview of the national and international data and research on adult sexual violence, with a particular focus on identifying the definitional and measurement issues that need to be considered when making comparisons of prevalence and incidence rates over time and between countries.